Multi-scale systems toxicology defines a KLF5-centered adverse outcome pathway linking DEHP exposure to pancreatic cancer progression and signaling programs relevant to therapy tolerance - Chen, Jihao; Pang, Huaxin; Wang, Jundan; Guo, Junhua; Huang, Ting; Zhou, Heran (Frontiers in Cell and Developmental Biology, 2026)
Di(2-ethylhexyl) phthalate (DEHP) is a ubiquitous plasticizer implicated in pancreatic carcinogenesis, yet the molecular initiating events and adverse outcome pathways (AOPs) linking exposure to disease mechanisms remain poorly resolved. In this study, we integrated a multi-scale systems toxicology framework—combining heterogeneous ensemble machine learning, Mendelian randomization (MR), molecular docking and molecular dynamics (MD), single-cell transcriptomics, and in vitro assays—to delineate a candidate mechanistic trajectory. A Tabular Prior-Data Fitted Network (TabPFN)-enhanced ensemble identified a six-gene pancreatic ductal adenocarcinoma (PDAC) signature (AUC = 0.946). Within this signature, MR provided suggestive evidence for a modest association between genetically predicted Krüppel-like factor 5 (KLF5) expression and pancreatic cancer risk (OR = 1.188, p = 0.046). Functional enrichment of DEHP–PDAC intersection targets highlighted pro-survival signaling modules, including PI3K–AKT- and MAPK-related pathways. Structure-based analyses supported the biophysical plausibility of a non-covalent DEHP–KLF5 interaction (−6.4 kcal/mol), and 100-ns MD simulations indicated a persistent binding mode with conformational accommodation. Single-cell analysis localized KLF5 predominantly to malignant ductal cells and, together with CellChat inference, was consistent with malignant cell-derived TGF-β- and MIF-related signaling. Network-based virtual knockout further suggested that KLF5 may contribute to sustaining a TGF-β/MMP7-linked matrix remodeling program. Consistently, DEHP exposure upregulated KLF5 and MMP7 and enhanced migration and invasion of PANC-1 cells. Collectively, these findings support a working AOP model linking DEHP-responsive KLF5-centered activity to extracellular matrix (ECM) remodeling and immunomodulatory communication, providing a mechanistic rationale that aligns with signaling programs characteristic of therapy-tolerant tumor niches, particularly PI3K–AKT-coupled survival signaling and TGF-β-linked stromal remodeling. Although these implications are hypothesis-generating, they highlight a potential avenue for future drug-response investigations.